Kinetic modelling of dissolution dynamic nuclear polarisation 13C magnetic resonance spectroscopy data for analysis of pyruvate delivery and fate in tumours. (28th November 2021) - Reynolds, Steven; Kazan, Samira M.; Anton, Adriana; Alizadeh, Tooba; Gunn, Roger N.; Paley, Martyn N.; Tozer, Gillian M.; Cunningham, Vincent J.
Abstract : Dissolution dynamic nuclear polarisation (dDNP) of 13 C‐labelled pyruvate in magnetic resonance spectroscopy/imaging (MRS/MRSI) has the potential for monitoring tumour progression and treatment response. Pyruvate delivery, its metabolism to lactate and efflux were investigated in rat P22 sarcomas following simultaneous intravenous administration of hyperpolarised 13 C‐labelled pyruvate ( 13 C1 ‐pyruvate) and urea ( 13 C‐urea), a nonmetabolised marker. A general mathematical model of pyruvate‐lactate exchange, incorporating an arterial input function (AIF), enabled the losses of pyruvate and lactate from tumour to be estimated, in addition to the clearance rate of pyruvate signal from blood into tumour, K ip, and the forward and reverse fractional rate constants for pyruvate‐lactate signal exchange, k pl and k lp . An analogous model was developed for urea, enabling estimation of urea tumour losses and the blood clearance parameter, K iu . A spectral fitting procedure to blood time‐course data proved superior to assuming a gamma‐variate form for the AIFs. Mean arterial blood pressure marginally correlated with clearance rates. K iu equalled K ip, indicating equivalent permeability of the tumour vasculature to urea and pyruvate. Fractional loss rate constants due to effluxes of pyruvate, lactate and urea from tumour tissue into blood ( k po, k lo and k uo, respectively) indicated that T 1 s and the average flip angle, θ, obtained from arterial blood were poor surrogates for these parameters in tumour tissue. A precursor‐product model, using the tumour pyruvate signal time‐course as the input for the corresponding lactate signal time‐course, was modified to account for the observed delay between them. The corresponding fractional rate constant, k avail, most likely reflected heterogeneous tumour microcirculation. Loss parameters, estimated from this model with different TRs, provided a lower limit on the estimates of tumour T 1 for lactate and urea. The results do not support use of hyperpolarised urea for providing information on the tumour microcirculation over and above what can be obtained from pyruvate alone. The results also highlight the need for rigorous processes controlling signal quantitation, if absolute estimations of biological parameters are required. Abstract : A general mathematical model incorporating an experimentally derived arterial input function was used to estimate tumour delivery, metabolism and efflux parameters for intravenously administered hyperpolarised 13 C‐labelled pyruvate in rats. 13 C‐labelled urea, as a nonmetabolised marker, was cleared from blood into tumour at the same rate as pyruvate. Analysis using a simpler precursor‐product (pyruvate‐lactate) model provided a lower limit estimate of T 1 for tumour lactate, as well as the pyruvate‐lactate exchange parameter, k pl . These techniques have the potential for clinical application.